A hedonic approach to estimate the price evolution of FTTH service: evidence from EU - Elias Aravantinos; Konstantin Petre; Dimitris Katsianis; Aris Chipouras; Dimitris Varoutas (International Telecommunications Society (ITS), 2022)
The price paid today for broadband bundling, is determined by a number of factors, such as broadband speed, premium content, inclusive call allowances, any value-added services, and it is important that people understand their usage requirements so they can identify the one that suits their need We found strong evidence that bundling proves to have a strong effect on tariffs, a dominant operator's strategy during the study's period, 2014-2020, allowing to allocate fixed costs across a range of services. Download Speed is positively significant to tariffs and increases broadband prices, such as a 10% increase in speed raises broadband prices by around 1.4%. Although broadband prices drop around 6.9%, operators emphasize their efforts to charge higher prices on TV bundles, specifically on plans combining broadband, voice telephony and TV that are 54% more expensive over standalone's plans, compared to the 36% of a previous 2014 study. Incumbents charge higher tariffs, around 20.1% compared to the new entrants, in an effort to pay off the fiber network deployment investments, as coverage continues to grow.
Keywords: 330; Hedonic prices; Bundling; Tariffs; Broadband; European Union; Regulation